2016
DOI: 10.1108/ijse-09-2014-0181
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of key predictors of performance of agricultural projects in Sub-Saharan Africa

Abstract: Purpose – The purpose of this paper is to examine the ways of improving performance of agricultural projects through stakeholder engagement and knowledge management in a Sub-Saharan context. Design/methodology/approach – Data were collected using a self-administered questionnaire from 342 agricultural projects in Mukono and Wakiso districts in Uganda. Descriptive statistics and inferential statistics were used in the analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…The questionnaires were distributed to the sampled farmers and data were collected based on a self-administered approach. Such an approach is consistent with the pertinent literature (Nkuruziza et al. , 2016).…”
Section: Methodssupporting
confidence: 89%
“…The questionnaires were distributed to the sampled farmers and data were collected based on a self-administered approach. Such an approach is consistent with the pertinent literature (Nkuruziza et al. , 2016).…”
Section: Methodssupporting
confidence: 89%
“…The study population comprised a total of 13,347 National Agricultural Advisory Services projects in Mukono and Wakiso districts of Uganda (Mutumba, 2017;Muhanguzi, Lutwama, & Mwiine, 2012, Nkurunziza, et al, 2016. Data was collected from stakeholders involved in agricultural projects in 18 sub-counties of Wakiso and Mukono districts in Uganda.…”
Section: Study Population Research Setting Sampling Design and Proced...mentioning
confidence: 99%
“…However, the performance of the agricultural sector in developing countries continues to stagnate despite the government's heavy investment in agricultural projects with the hope of stimulating growth, employment, and economic development for over a decade (Meijerink & Roza, 2007;Bjornlund et al, 2020). Surprisingly, Africa's economic growth rate and project performance outcomes are above the global average growth rate, but these parameters do not translate into social and economic protection for rural families and community livelihood (Da Silva, 2014;Nkurunziza et al, 2016). Over time, government stakeholders, policymakers, and researchers around the world are devising means of project improvement in various entrepreneurial ecosystems with superficial knowledge of agricultural project management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it shows that project human resource management and project stakeholder management have the strongest association with enterprise-wide KM. Another relationship was studied by Nkuruziza et al (2016) that concluded that knowledge management and stakeholder involvement are significant predictors of project performance in the agricultural sector. The project team, model farmers, and other agricultural project stakeholders should be equipped with tacit and explicit knowledge and involved in the decision-making process for project success.…”
Section: Content Analysis Of Sample Textsmentioning
confidence: 99%